Strengthening the Tension of Socio-Scientific Issues Based Learning to Promoting Democratic Life : A Systematic Review - Firdaus, Laras; Hunaepi, Hunaepi; Fitriani, Herdiyana; Samsuri, Taufik (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Currently, Socio-Scientific Issues (SSI) are a learning approach that is widely used by educators, not only helping students to understand a topic but also improving students' scientific literacy skills, such as critical thinking, argumentation skills, and decision-making. Various studies related to SSI have been published but cannot provide specific recommendations for future SSI studies. Therefore, a research systematic review of literature related to SSI was carried out to identify and determine research trends related to SSI as a basis for conducting further SSI studies. In conducting this literature review, we collected SSI-related information from the Google Scholar publication database using socio-scientific issues as search keywords. In collecting and selecting it using PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis), 155 articles were found that met the predetermined criteria for further analysis using Vosviewer. From the results of the analysis that has been done, decision-making is an item that has been studied a lot related to SSI. Thus, this item (decision-making) is recommended for further study.